2002
DOI: 10.2307/1423432
|View full text |Cite
|
Sign up to set email alerts
|

Misremembering Pictured Objects: People of All Ages Demonstrate the Boundary Extension Illusion

Abstract: In the boundary extension illusion, subjects recollect more of a photographed scene than was originally shown. In this study, first- and fifth-grade children, young adult college students, and older adults studied 4 one-object or 4 two-object picture stimuli for 15 s each. Immediately after each visual scene was shown, the subjects drew it from memory inside a rectangle that was the same size as the previous picture. This study demonstrated that all age groups, from young children to older adults, were suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 0 publications
6
43
0
2
Order By: Relevance
“…Here the task for participants was natural and easily understood even among boys who might have difficulty with some testing situations. The finding of extremely high degrees of boundary extension in these groups supports those of Seamon et al (2002) in demonstrating boundary extension in people of all ages. In Seamon et al's study, younger participants actually showed greater levels of boundary extension than college students.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Here the task for participants was natural and easily understood even among boys who might have difficulty with some testing situations. The finding of extremely high degrees of boundary extension in these groups supports those of Seamon et al (2002) in demonstrating boundary extension in people of all ages. In Seamon et al's study, younger participants actually showed greater levels of boundary extension than college students.…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that the greater richness of the original memory helps them discriminate it from the picture presented at test, thus guarding against normalization in memory, though not against the initial perceptual process of extension. EXPERIMENT 2 Seamon et al (2002) used a drawing task to demonstrate reliable boundary extension both in children and elderly participants. In general they found that the degree of extension in these populations was greater than in college students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this initial demonstration, much research has been done showing the generality of this effect. For example, boundary extension is robust to various tasks beyond drawing, such as rating and border adjustment (e.g., Intraub et al, 1992Intraub et al, , 2006, and to different image sets (Candel et al, 2003;Daniels and Intraub, 2006); it operates over a range of timescales from minutes to hours (Intraub and Dickinson, 2008); and it is found in both young children and older adults (Candel et al, 2004;Seamon et al, 2002). Interestingly, boundary extension occurs even when observers are blindfoldedthey explore space with their hands -suggesting an important link between the representations of space across sensory modalities (Intraub, 2004).…”
Section: Behavioral and Neural Aspects Of Boundary Extensionmentioning
confidence: 99%
“…심지어는 피실험자들에 게 이러한 왜곡경향이 있음을 미리 알려주고 실험을 진행한 경우에도 경계확장의 정도는 약해졌지만 제거되지 않았다고 한다 (Intraub and Bodamer, 1993). 또한, 기억유지 시간 (retention time)이 1초 정도로 짧은 경우에도 관찰된다고 하며 , 부정적인 감성을 유발하는 사 진이든 아니든 상관없이 (Candel et al, 2003) 다양한 연 령층의 피실험자들에게서 관찰된다고 한다 (Seamon et al, 2002).…”
Section: 장필식 大韓人間工學會unclassified